Impacts Environnementaux De L’hévéaculture Dans Le Departement D’aboisso, Sud-Est De La Côte d’Ivoire - Houphouët Jean Claude Diby; Simplice Yao Koffi; Joseph Pierre Assi-Kaudjhis (European Scientific Journal, ESJ, 2017)
The good physical, human, and political conditions enjoyed by the Aboisso Department, located in the southeast of Côte d'Ivoire, have promoted the expansion of rubber as a commercial crop. This traditional culture is currently undergoing upgrades such that its success is accompanied by mutation and various consequences in the area. This study however aims to evaluate the consequences of this culture at the environmental level. Specifically, it shows the type of vegetation and climate rubber is grown. Based on the literature, the survey data, and the analysis of climate data through the mapping of rainfall values and trends, this study has made it possible to observe changes at the environmental level in the area. The analysis of these results indicates that rubber had corrected floristic and rainfall deficits.